Enhancing Fair Use in Protecting Appropriated Artworks: A Comparative Analysis of Safeguarding Indonesian Copyright Law - Caitlynn Nadya Aurelia; Velliana Tanaya; Fajar Sugianto; Atsuko Yamamoto (Universitas Negeri Semarang, 2025)
Appropriated artwork refers to the practice of using pre-existing objects or images into new works of art with little or no significant changes to the original form. This trend developed into the Pop Art movement, where one of the characteristic features was the use of images from mass media, as seen in the works of Andy Warhol, including the transformation of Campbell's soup cans into iconic works of art. Although widely appreciated, this work has drawn criticism regarding copyright infringement, raising the question: where do one artist's rights draw on another? To what extent is the appropriation of copyright protected works considered legal without violating the rights of the original creator? The research results show that the two legal systems differ significantly in the aspects of exclusive rights, moral rights, protected works, exceptions, and duration of protection. The challenge in understanding fair use lies in determining the boundaries between the rights of one artist and another. The fair use doctrine assesses four main factors: the purpose and character of the use, the nature of the original work, the proportion of the work used, and the impact on the market. Courts in the US often favor fair use if elements of transformation are identified, measuring the extent to which the appropriated work carries elements of originality or new creativity. Indonesia could consider adopting the fair use doctrine by adapting the concept through ministerial regulations or other implementing regulations.